1967
DOI: 10.1161/01.res.21.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between Automaticity and Conduction in Purkinje Fibers

Abstract: Microelectrode studies of transmembrane potentials of canine Purkinje fibers show that phase-4 depolarization causes voltage-dependent changes in conduction and responsiveness similar to those occurring during repolarization at comparable levels of potential. Abnormalities ranged from simple slowing of conduction to decrement, unidirectional and bidirectional block, and unexcitability. Reentrant excitation also developed. Significant conduction disturbances usually appeared at -75 to -70 mv; decrement and adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(71 citation statements)
references
References 38 publications
3
68
0
Order By: Relevance
“…As with any experimental observation, the applica- 30 Although these mechanisms may not have played a major role in the initiation or maintenance of ventricular fibrillation in the animals with nonischemic myocardium in our study, their potential contribution cannot be excluded.…”
Section: Discussionmentioning
confidence: 63%
“…As with any experimental observation, the applica- 30 Although these mechanisms may not have played a major role in the initiation or maintenance of ventricular fibrillation in the animals with nonischemic myocardium in our study, their potential contribution cannot be excluded.…”
Section: Discussionmentioning
confidence: 63%
“…Singer et al (4) demonstrated that phase 4 depolarization in Purkinje fibers results in varying degrees of conduction depression. Thus, as impulses arrive at a cell progressively later during spontaneous phase 4 depolarization, take-off potential will be decreased, and hence total action potential amplitude, maximal rising velocity of phase 0, and conduction velocity will fall.…”
Section: Bailey Greenspan Elizari Anderson Fischmentioning
confidence: 99%
“…of action -potentials evoked in Purkinje fibers are, for practical -purposes, entirely dependent on membrane voltage at the time of activation (24), no matter whether a given membrane voltage has been reached: (a) during repolarization of a normal action potential, (b) by generalized depolarization of the membrane, or (c) by phase 4 depolarization. Augmented automaticity localized -to one branch of a Purkinje fiber could cause delayed Londuction and block of impulses propagating into this branch; this conduction delay can be unidirectional and -cause reentry (20). Application of lidocaine could diminish automaticity and thereby speed conduction and abolish reentry.…”
Section: Effects Of Lidocaine On Automaticity In Purkinje Fibersmentioning
confidence: 99%
“…As pointed out previously (18)(19)(20), ventricular arrhythmias are best understood in terms of alterations in automaticity, conductivity, and the associated changes in the electrophysiological properties of the Purkinje fiber. Automatic ventricular rhythms almost certainly originate in the Purkinje fibers (PF) and the impulse in reentrant ventricular arrhythmias frequently must utilize these fibers as a portion of the reentrant circuit.…”
Section: Introductionmentioning
confidence: 95%